Los valores culturales y el desarrollo de habilidades sociales en los estudiantes de educación básica superior de la escuela de Educación Básica Dr. Leonidas García Ortiz de la ciudad de Riobamba - Tigasi Tigasi, Aida Blanca (2021)
This research aimed to determine cultural values and the level of social skills development of 9th and 10th higher education students parallels A and B of the School of Basic Education “Dr. Leónidas García Ortiz” at the city of Riobamba, the beneficiaries are the students it should be emphasized that cultural values are those that represent a set of beliefs, languages, traditions, and relationships that identify roots of different ethnicities when participating in different activities and within social skills we can say that they are behavioral strategies, capacities to apply such behaviors that help us solve a social situation. Methodologically we worked, with a quantitative approach, non-experimental research design, the type of research was descriptive and correlational, by the time it was transversal, by the objectives it was basic and by the place was field, the sample was intentional non-probabilistic type establishing itself between the two parallels to 120 students including 64 women and 56 men. For data collection it was the AD Hoc survey technique for the independent variable and Elena Gismero's Social Skills Scale (EHS) psychological reagent for teens, for the dependent variable. Finally, the following conclusions are drawn from the research: in cultural values, students demonstrate practicing values in a high percentage, in social skills, students demonstrate a low level where problems of depression or emotional psychological may exist, affecting the educational field.